Flow Cytometric Quantification of HIV-1-Infected Cells Expressing Either Abortive or Elongated HIV-1 Transcripts Using Flow-FISH - Shirley Man; Teunis Geijtenbeek; Neeltje Kootstra (Bio-Protocol)
The persistence of the HIV-1 reservoir remains the ultimate obstacle in achieving a cure. Cure strategies targeting the HIV-1 reservoir are under development, and therefore, finding ways to improve the detection of the reservoir is crucial. Several reservoir detection techniques exist to assess different markers of the HIV-1 reservoir, such as PCR-based assays and protein-based flow cytometric methods. We developed a flow cytometry-fluorescent in situ hybridization (flow-FISH) approach that assesses HIV-1 at the transcriptional level. Using a combination of probes that target either the HIV-1 trans-activation response (TAR) region and 5′ long terminal repeat (LTR) or the Gag sequence, our assay distinguishes between infected cells expressing abortive or elongated HIV-1 RNAs. This assay utilizes the branched-DNA method to amplify the fluorescent signal of the hybridized RNA probes and can be used directly for thawed or cultured cells, with the option to include surface antibody staining. Cellular expression of abortive and/or Gag HIV-1 RNAs is measured by flow cytometry. Our flow-FISH approach gives insight into the transcriptional dynamics of the HIV-1 reservoir and allows for the characterization of latently infected cells.